2006
DOI: 10.1186/1472-6963-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Profit and loss analysis for an intensive care unit (ICU) in Japan: a tool for strategic management

Abstract: Background: Accurate cost estimate and a profit and loss analysis are necessary for health care practice. We performed an actual financial analysis for an intensive care unit (ICU) of a university hospital in Japan, and tried to discuss the health care policy and resource allocation decisions that have an impact on critical intensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
122
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 24 publications
4
122
2
3
Order By: Relevance
“…Past trials have failed to support the efficacy of activating patients to manage their HF by learning self-management skills, 1216 but they have been limited by weak designs. The size, duration, methodological rigor, and representativeness of HART position it well to provide more conclusive results.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Past trials have failed to support the efficacy of activating patients to manage their HF by learning self-management skills, 1216 but they have been limited by weak designs. The size, duration, methodological rigor, and representativeness of HART position it well to provide more conclusive results.…”
Section: Commentmentioning
confidence: 99%
“…1216 All are limited by small sample sizes (range: 70–197 patients), short durations (typically 2 to 3 contacts), and inadequate evaluations of maintenance of treatments effects (typically only 0–3 months). Only one trial showed benefit on a clinical endpoint (death or hospitalization) 16 but baseline differences in prognostic factors limit interpretation. Thus, the value of patient self-management programs for patients with HF is questionable.…”
mentioning
confidence: 99%
“…Although tested in efficacy trials, it is postulated that these new innovations need to be applied and modified to specific clinical settings to be routinely available in health care. The NPM has been applied to process evaluation in decision support technologies, telemedicine, nurse-led heart failure clinics, language interpretation services, and tuberculosis treatment (Atkins, Lewin, Ringsberg, & Thorson, 2011; Elwyn, Legare, van der Weijden, Edwards, & May, 2008; May, 2006; May, Mair, Dowrick, & Finch, 2007). Although not specific to group psychotherapy delivery models, the NPM has been applied to implementation of national mental health standards, such as suicide prevention in primary care settings and trials of a new psychosocial problem solving therapy (Gask, Rogers, Campbell, & Sheaff, 2008; May, Mair, et al, 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Contextual integration describes how IPSRT-G utilizes resources and changes infrastructure, policies, and procedures within the psychiatric practice. Contextual integration considers how the allocation of resources for the IPSRT-G may be perceived by other programs, in context of increasingly finite resources (May, 2006; May, Finch, et al, 2007; May, Mair, et al, 2007). The NPM concept descriptions, factors assessed and tools utilized are listed in Table 1.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Sin embargo, el mé todo para establecer dicha cifra consistió en: i) identificar y cuantificar bloques de costos directos como personal, servicios clínicos de apoyo, y bienes y servicios de consumo corriente; ii) establecer la ponderació n de estos recursos en el total, lo que resultó en 85%; y iii) suponer que el 15% restante era costo indirecto estructural [29]. Metodologías má s minuciosas como el costeo ABC (Activity Based Costing) aplicada a una unidad de cuidados intensivos en un hospital universitario de Japó n permiten establecer una participació n en el costo total de 19% para los costos indirectos estructurales [30]. Por otro lado, Sanders A, et al, aplicando tambié n una metodología ABC al proceso de transfusiones de sangre en pacientes quirú rgicos, en dos hospitales de EE.UU.…”
Section: Discusió Nunclassified